The Role of Sex Hormones on Bone Mineral Density, Marrow Adiposity, and Muscle Adiposity in Middle-Aged and Older Men - Xu, Li; Zhao, Qian; Li, Kai; Zhang, Yong; Wang, Chao; Hind, Karen; Wang, Ling; Liu, Yandong; Cheng, Xiaoguang (Frontiers in Endocrinology, 2022)
Purpose The etiology of age-related bone loss is less clear in men. This study is aimed to observe the variations of endogenous sex hormone concentrations with increasing of age in men, and investigate their relations to bone mass, marrow adiposity, and muscle adiposity. Methods A total of 199 community-dwelling Chinese men (aged 41 to 82 years) were included and measured of serum total estradiol, total testosterone, and follicle-stimulating hormone (FSH) concentrations by enzyme-linked immunosorbent assay (ELISA). Vertebral trabecular volumetric bone mineral density (vBMD) was measured by quantitative computed tomography for all participants, and vertebral marrow fat content and erector muscle fat content were quantified by Chemistry-shift-encoding magnetic resonance imaging in 62 participants. Results In this population, FSH concentration increased (p < 0.001) gradually with aging. Lower vBMD was independently associated with higher FSH concentration (β = -0.216, p < 0.001), but not with total estradiol or total testosterone. For each standard deviation increase in FSH there was a 50% higher risk of an individual having osteopenia or osteoporosis (vBMD < 120 mg/cm3). Marrow fat content and erector muscle fat content were greater in osteopenic and osteoporotic men, but there were no associations with sex hormones concentrations. Conclusion In summary, FSH but not total estradiol or total testosterone is related to vertebral trabecular vBMD in middle-aged and older Chinese men. Neither marrow adiposity nor muscle adiposity is associated with sex hormones.